TEORI HABIT PERSPEKTIF PSIKOLOGI DAN PENDIDIKAN ISLAM - M. Miftah Arief; Dina Hermina; Nuril Huda (Ri'ayah: Jurnal Sosial dan Keagamaan, 2022)
Habit are the result of automatic cognitive processes, developed through extensive repetition, well-learned and do not require conscious effort. The habit according to Islamic education is an effective method or way to instill religious values. Habit is a series of repeated actions by a person for the same thing and takes place without a thought process. Habit, when associated with learning, is oriented and can be understood as a series of behaviors that are carried out consistently/repeatedly by students in their learning activities. Almost all education assesses the learning success of students in terms of value indicators alone, if the student's score is high then the teaching and learning process is considered successful. This is basically contrary to intelligence theory and Bloom's Taxonomy theory, the concept of three hierarchical models used to classify children's educational development objectively. The need for understanding the concept of habit is very necessary to straighten out the problems that assume that the success of education is seen from the value of the subject. If learning is oriented to the concept of habit, then in the learning and learning process there is no term coercion or pressure, as well as learning outcomes of course not only seen in the aspect of value, but balance with behavior after learning will also be an indicator of success in education. This type of research is library research which is based on literature studies, extracting and collecting data using documentation techniques that are oriented towards various studies and relevant theories so that later information data is collected regarding. Building good habits is a fundamental problem for human life because our behavior is strongly influenced by our habits. Routine/ Consistent/ Istiqomah, are the behavior patterns we repeat most often, literally etched into our neural pathways. Through repetition and practice, it is possible to form (and maintain) new habits in which new response mechanisms are formed. A good way to start forming new habits is to keep them easy and simple.